Ruthenium phthalocyanines with axial carboxylate ligands. Synthesis and function in solar cells based on nanocrystalline TiO2 - Yanagisawa, M; Korodi, F; He, JJ; Sun, LC; Sundström, Villy; Akermark, B (Journal of Porphyrins and Phthalocyanines, 2002)
The synthesis and characterization of phthalocyaninato-ruthenium (PcRu) complexes with potential functional axial ligands are described. The solubility of these PcRu complexes was much improved compared to their parent phthalocyanines without Ru, enabling purification by normal flash column chromatography and also NMR measurements in common solvents (e. g. DMSO-d(6) and CDCl3). Adsorption of these phthalocyanine dyes onto the surface of a semiconductor through the carboxyl group(s) in the axial ligands prevents to some extent formation of H-aggregates, which is typical for phthalocyanines. It also prevents stacking of the dye molecules on the surface. The photovoltaic behavior of sandwich solar cells based on nanostructured TiO2 films sensitized by these PcRu complexes was studied under irradiation with visible light. For a solar cell based on bis(4-carboxypyridine)-phthalocyaninato ruthenium(II) (1) sensitized nanoporous-nanocrystalline TiO2, a monochromatic incident photon-to-current conversion efficiency (IPCE) of 21% was obtained at 640 nm. The overall conversion efficiency (eta) was 0.61%, which is one of the best results for a solar cell based on a phthalocyanine dye. For a cell based on (4-carboxypyridine)-(4-(2-ethoxy)ethyloxycarbonylpyridine)-2,3,9,10,16,1 7,23,24-octa(n-pentyloxy)-phthalocyaninato ruthenium(II) (5) sensitized TiO2, a IPCE of 6.6% at 640 nm and eta of 0.58% were obtained.
The information about affiliations in this record was updated in December 2015. The record was previously connected to the following departments: Chemical Physics (S) (011001060)
Keywords: dyes for solar cells; ruthenium phthalocyanines; axial ligands; nanotrystalline TiO2